The effects of a diet and feeding frequency on peripheral nutrient supply and growth traits of the lamb - Evans, Judith A. (1999)
Tissue protein synthesis requires a simultaneous supply of energy and amino acids. The effect of altering diet and frequency of feeding on patterns of amino acid and acetate supply to peripheral tissues and the consequent effects on growth and carcass composition was investigated in growing lambs. A rumen 'asynchronous' diet with respect to the ratio of the rate of release of organic matter (OM) and nitrogen (N) was fed once daily (AD) or hourly (AR) and a more 'synchronous' diet was fed once daily (SD) to individually penned growing lambs (n=30) for 16 weeks. Plasma concentrations of acetate, amino acids and insulin were more constant throughout the day in animals fed AH compared to those fed AD. Those fed SD or AD had similar, large pulses in plasma acetate concentration following feeding. Animals fed AH had increased growth rates and greater amounts of carcass crude protein compared to those fed AD (P<O.OO1). Animals fed SD had faster growth rates with a higher amount of carcass crude protein and fat deposition than those fed AD (P>O.1). Synchronous diets formulated to have either slow (SS) or fast (FP) release of OM and N into the rumen were fed hourly (SSH or FFH) or once daily (SSD or FFD) to individually penned growing lambs (n=28) for 10 weeks. Plasma concentrations of acetate and insulin in groups fed once daily, increased after feeding, remaining elevated for longer in animals fed SSD. Amino acid concentrations decreased following feeding. Once daily fed animals tended to have greater amounts of crude protein in the carcass and generally heavier muscles than those fed hourly, particularly those fed SS. Animals fed AH had significantly higher feed intakes in the first experiment compared to those fed the diets once daily (P<O.OO1) which may be why these animals grew better and deposited more carcass protein than those fed once daily. It was thought that a pulse in acetate following feeding may contribute to an enhanced growth and carcass protein in ruminants. When sodium acetate was infused into growing lambs, intravenously, to raise the concentrations of plasma acetate similar to the pulse in acetate concentrations observed in the plasma of sheep following once daily feeding, no increase in whole-body protein synthesis was observed. The effect of temporal changes in the peripheral nutrient supply on protein synthesis in the ruminant requires further investigation.